INTELLIGENT MOTION BLUR SYSTEM FOR SOCCER PLAYERS - Nada Thanoon Ahmed; Maysaa Hameed Abdulameer; Abbas Akram Khorsheed; Nadia Mahmood Hussien; Yasmin Makki Mohialden (Journal Park Publishing, 2023)
Motion blur is a very important part of how we see moving things. This effect shows up as a visible trail along the path of the object. It is caused by the way that film and digital cameras handle relative motion and light integration. In this paper, we developed a software method to create motion blur on the YasminadNadia 25th Arabian Gulf Cup Iraq dataset, which has the faces of Arabian Gulf Cup Iraq players and is made public on the websites Kaggle and GitHub. We also found the best kernel motion blur size for each image in the dataset. The proposed method was made using the openCV, NumPy, and pillow libraries.
Keywords: Intelligent motion, video Captureing, Blur Image, Gulf Cup Dataset, open CV.